Performance Evaluation of Exchange Traded Fund in The Indonesia Stock Exchange - Adi Cahya Stefanus; Robiyanto Robiyanto (Universitas Pendidikan Ganesha, 2020)
This study aims to evaluate the performance of the Exchange Traded Fund (ETF) index in the Indonesia Stock Exchange by using the Treynor Ratio, Sharpe Ratio, Sortino Ratio, Jensen Alpha, Information Ratio, and Omega Ratio. This research uses a quantitative descriptive approach, and the data source to be applied in this research is secondary data, where the data to be used is the ETF listed on the IDX. The data collection technique will be carried out with a documentation study. There are 12 ETFs to be evaluated. The data used in this study are the weekly closing price and risk-free investment that is represented by the BI rate from January 2018 to December 2019. The result of this study shows that there are only two of the Exchange Traded Fund that has better performance than risk-free investment if it is calculated by using the Sharpe Ratio, Sortino Ratio, Information Ratio, and Omega Ratio. In contrast, the Treynor Ratio and Jensen Alpha show negative value or worse than risk-free investment.